Coagulase Typing and spa Typing of Methicillin Resistant Staphylococcus aureus: Relatedness Among Patients' and Carrier Strains (Bangladesh Journal of Medical Microbiology, 2016)
This study was carried out to determine the types of Methicillin-Resistant Staphylococcus aureus (MRSA) by two typing systems, Coagulase typing and spa typing and to identify relationship between types of MRSA strains isolated from patients and hospital staff carriers. A total of 40 MRSA strains, 33 from cases of wound infection and 7 from anterior nares of hospital staffs were investigated. Coagulase typing showed that all the MRSA strains isolated from patients were coagulase type VI and all the strains isolated from carriers were coagulase type VII. In spa typing, seven spa types were detected such as S4, S6, S7, S8, S9, S10 and S11. Predominant spa type in patients was S7 detected in 15 (45.45%) MRSA isolates, followed by S4 in 8 (24.24%) strains and S6 in 5(15.15%) strains. Other spa types detected in patients in small numbers were S8 (3.03%), S9 (3.03%), S10 (6.06%) and S11 (3.03%). While in strains of MRSA isolated from carriers, only two types S4 and S9 were detected. Both the spa types identified from carriers were also detected in a total of 9 (27.2%) of MRSA strains isolated from patients.Bangladesh J Med Microbiol 2008; 02 (01): 3-7DOI: http://dx.doi.org/10.3329/bjmm.v2i1.21780